2019
DOI: 10.1177/1060028019864574
|View full text |Cite
|
Sign up to set email alerts
|

Amifampridine for the Management of Lambert-Eaton Myasthenic Syndrome: A New Take on an Old Drug

Abstract: Objective: The purpose of this article is to review the literature for both 3,4-diaminopyridine (3,4-DAP) and amifampridine for the treatment of Lambert-Eaton myasthenic syndrome (LEMS). Amifampridine (Firdapse) is the salt form of 3,4-DAP and was approved by the Food and Drug Administration for the treatment of LEMS. Data Sources: PubMed, TRIP database, and EMBASE searches were conducted without a back date (current to June 2019) utilizing the following search terms: amifampridine, 3,4-diaminopyridine, and La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…3,4-diaminopyridine (3,4-DAP) is a non-specific voltage-dependent potassium channel (Kv1.5) blocker, which causes depolarization of the presynaptic membrane at the NMJ and delays nerve repolarization, thus increasing quantal release of ACh. It is used in the treatment of Lambert-Eaton myasthenic syndrome (LEMS) and congenital myasthenia ( 84 , 85 ). A recent phase IIb study in 10 adult patients with MuSK-MG, showed that it was safe and an improvement was seen across both objective measures of muscle strength and patient reported outcomes ( 86 ).…”
Section: Treatment Of Jmgmentioning
confidence: 99%
“…3,4-diaminopyridine (3,4-DAP) is a non-specific voltage-dependent potassium channel (Kv1.5) blocker, which causes depolarization of the presynaptic membrane at the NMJ and delays nerve repolarization, thus increasing quantal release of ACh. It is used in the treatment of Lambert-Eaton myasthenic syndrome (LEMS) and congenital myasthenia ( 84 , 85 ). A recent phase IIb study in 10 adult patients with MuSK-MG, showed that it was safe and an improvement was seen across both objective measures of muscle strength and patient reported outcomes ( 86 ).…”
Section: Treatment Of Jmgmentioning
confidence: 99%
“…3,4-DAP is the FDA-approved first-line treatment for patients with Lambert-Eaton Myasthenic Syndrome (LEMS; (7)(8)(9)(10)). Although 3,4-DAP is canonically thought to mediate its effects by partially blocking presynaptic Kv channels, a previous report that millimolar concentrations of 3,4-DAP could have off-target effects on Cav1 channels led to the question of whether 3,4-DAP mechanisms of action at therapeutic concentrations (estimated to be in the low micromolar range) involve Cav1 channels.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and animal model studies suggest that neuromuscular transmission, and subsequently muscle strength, can be improved by the use of 3,4-diaminopyridine (3,, which is a small molecule that acts as an antagonist at voltage-gated potassium (Kv) channels. 3,4-DAP was recently approved by the FDA to treat LEMS (7)(8)(9)(10) and has been shown to be effective at increasing neuromuscular strength in patients with LEMS (11)(12)(13)(14). However, 3,4-DAP has dose-dependent side effects that restrict the amount that patients take to relatively small doses, which prevents full symptomatic relief in many patients with LEMS (15,16).…”
mentioning
confidence: 99%
“…Міастенічні синдром (МС) Ламберта-Ітона -рідкісне аутоімунне захворювання, яке впливає на вивільнення пресинаптичного ацетилхоліну, яке індукується аутоантителами проти потенціал-керованих кальцієвих каналів [1,2]. За оцінками, поширеність МС Ламберта-Ітона у всьому світі становить від 3 до 4 на мільйон населення [3,4]. Він може бути паранеопластичним (ПМС) або непаранеопластичним (НПМС).Мета: провести аналіз особливостей перебігу, діагностики та лікування синдрому Ламберта -Ітона з метою поліпшення якості онкологічної допомоги пацієнтам.Матеріали та методи: В роботі наведено результати аналізу експериментальних та клінічних досліджень в пошукових системах Scientific Indexing Services, PubMed, Elibrary, Hinari, власні клінічні спостереження і дослідження.…”
unclassified
“…Міастенічні синдром (МС) Ламберта-Ітона -рідкісне аутоімунне захворювання, яке впливає на вивільнення пресинаптичного ацетилхоліну, яке індукується аутоантителами проти потенціал-керованих кальцієвих каналів [1,2]. За оцінками, поширеність МС Ламберта-Ітона у всьому світі становить від 3 до 4 на мільйон населення [3,4]. Він може бути паранеопластичним (ПМС) або непаранеопластичним (НПМС).…”
unclassified